Development of Audio Visual Teaching Materials for Folk Songs Charged with Local Wisdom in Learning Poetry Texts for Class VIII Students of SMPN 14 Malang - Redin Surya Bagas Santoso; Heri Suwignyo; Nita Widiati (Randwick International of Education and Linguistics Science Journal, 2022)
The covid-19 pandemic era has an important influence on the learning process on students and teachers and as a form of educator transition in digital era learning. The use of online applications in learning activities helps teachers learn online / distance, but the progress found by some students sometimes do not pay maximum attention to learning or the use of conventional teaching materials is not well understood by students. So it is difficult for teachers to achieve learning competencies and monitor to the maximum. The need for creative and innovative teaching materials in order to create interesting and relevant learning for students. This study aims to produce audio-visual teaching materials for learning to write poetry with implementing the essence of the content of local wisdom and folk songs in it, teaching materials are presented in the form of audio-visual displays in their use, so that this teaching material produces decent learning for class VIII students. This study used a 4-D research model proposed by Thiagarajan. The description of the developed product includes: shape, content and appearance. The results of validation tests and field trials show that this product is very suitable for use in learning to write poetry to support creative and independent students